Characteristics of Sudan Iii-Poly(N Vinylcarbazole) Composite Film for Optical Sensor Application - Taunaumang, Heindrich; Dumais, Raindy Xaverius; Pondaag, Jinno (IPTEK The Journal for Technology and Science, 2014)
Photo-responsive molecule Sudan III has been developed in form of thin film to pursue their excellent properties especially for optical sensor device application. However, thin film of Sudan III possesses a weak mechanical property. And therefore in order to enhance this functional property of the Sudan III molecule was embedded within polymer matrix to form composite material. In this research, the thin films composite of Sudan III-Poly(N-Vinylcarbazole) or Sudan III/PVK were fabricated by using casting and spin coating methods. The structure of Sudan III-Poly(N-Vinylcarbazole) composite material were characterized by using FTIR, XRD measurement and for the optical property (absorbance) by UV-VIS measurement. In this paper the experiment results are presented